2011
DOI: 10.1016/j.powtec.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the densification of a vibrated sand packing

Abstract: International audienceTwo techniques have been used to analyze the densification of silica sand by horizontal sinusoidal vibrations of frequency f = 50 Hz for relative accelerations between 0 and 6: the quantitative analysis of motion observed through the transparent wall, and the altitude map of the free top surface of the sample. The first technique was used to analyze the transient regime: during the first 10 s, slight densification occurs at the bottom of the powder bed, while the upper part enters convect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…24 Another option is to restrict the data collection to the surface of the granular system, with the disadvantage that bulk properties can differ significantly from the behavior at the surface. [25][26][27][28][29][30] If the volume fraction of the particles is sufficiently low, stereo-camera or volumetric methods can be used to capture three-dimensional (3D) dynamics. [31][32][33] If the particles are optically transparent, there exist two additional options.…”
Section: Current Challengesmentioning
confidence: 99%
“…24 Another option is to restrict the data collection to the surface of the granular system, with the disadvantage that bulk properties can differ significantly from the behavior at the surface. [25][26][27][28][29][30] If the volume fraction of the particles is sufficiently low, stereo-camera or volumetric methods can be used to capture three-dimensional (3D) dynamics. [31][32][33] If the particles are optically transparent, there exist two additional options.…”
Section: Current Challengesmentioning
confidence: 99%
“…Although it has been reported that particle mineralogy and shape both affect the performance of an ultrasonic compaction 3 process [12,13], the influence of geological materials is unclear. There has been conflicting evidence between different studies with respect to the influence of vibrations on densification [14], and it has been proposed that significant differences between the physical properties of the particles, such as grain size and density, are contributory factors. It has also been reported that there is a significantly increased density and particle distribution uniformity within the granular material achieved when ultrasonic excitation is superimposed on the compaction process [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the vibration of granular material such as sand particles, it is known that there is a stage at which the particles begin to behave more like a fluid than a solid. This can be referred to as the fluidisation transition [14]. Convection motion has been shown to be influential in how the particles move from a solid-like state to fluid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations